Punicalagin Alleviates Psoriasis by Inhibiting NF-κB-Mediated IL-1β Transcription and Caspase-1-Regulated IL-1β Secretion - Lipeng Tang; Lipeng Tang; Lipeng Tang; Tong Li; Tong Li; Tong Li; Tong Li; Bowen Zhang; Zihao Zhang; Xiaoyi Sun; Ying Zhu; Ying Zhu; et al. (Frontiers Media S.A., 2022)
Psoriasis is a chronic and inflammatory skin disorder characterized by inflammation and epidermal hyperplasia. Punicalagin (PUN) is a main active ingredient of pomegranate (Punica granatum L.) peel with multiple biological activities, such as antibacterial, antioxidant and anti-tumor effects. However, the potential effect of PUN on psoriasis remains unknown. In this study, we want to investigate the pharmacological effect of PUN on psoriasis by using imiquimod (IMQ)-induced psoriatic mice model in vivo and tumor necrosis factor a (TNF-α) and interleukin-17A (IL-17A)-stimulated HaCaT cells in vitro. Our results showed that PUN can effectively alleviate the severity of psoriasis-like symptoms. Mechanistically, PUN potently suppresses the aberrant upregulation of interleukin-1β (IL-1β) and subsequent IL-1β-mediated inflammatory cascade in keratinocytes by inhibiting the nuclear factor kappa B (NF-κB) activation and cleaved caspase-1 expression in vitro and in vivo. Taken together, our findings indicate that PUN can relieve psoriasis by repressing NF-κB-mediated IL-1β transcription and caspase-1-regulated IL-1β secretion, which provide evidence that PUN might represent a novel and promising candidate for the treatment of psoriasis.